Diagnostic Role of Fine Needle Aspiration Cytology in the Breast Lump With its Correlation with Histopathology - Khatun, Hazara; Enam, Suraiya; Hussain, Maleeha; Begum, Monowara (TAJ: Journal of Teachers Association, 2011)
This study was carried out to evaluate the accuracy of FNAC and its role in palpable breast lumps for the early surgical management in outdoor and indoor patients of Dhaka Medical College during the period of January to December 2000. FNAC was performed on 310 patients who presented with palpable breast lumps. Histopathology was available in 122 cases, among which cytologically diagnosed benign cases were 106 proved so histologically in 105 (99.05%) cases but catagorized correctly in 99 cases. There was false negative diagnosis in one case. All 14 cases diagnosed as malignant in cytological examination were confirmed as such histologically. Two cases reported as suspicious for malignancy in cytological diagnosis, was proved malignant histologically. False positive diagnosis was made in one case. The accuracy of FNAC in the diagnosis of breast lump is quite satisfactory and can be compared with histopathological diagnosis. DOI: http://dx.doi.org/10.3329/taj.v14i2.8388 TAJ 2001; 14(2): 65-69